Analysis of Rhodamine B content in shrimp paste at Ciroyom Market, Bandung City, West Java, Indonesia - Robby Gus Mahardika; Farhan Baehaki; Heru Agung Saputra; Septiani Yusuf (Universitas Lampung, 2022)
According to regulation number 722/MENKES/Per/IX/88 of the Minister of Health of the Republic of Indonesia, Rhodamine B is one of the dangerous dyes, and its use in food products is prohibited. Rhodamine B can cause adverse health effects including irritation, impaired liver function, and liver cancer. Although it has been banned, the use of Rhodamine B is still prevalent in the community's food supply, including shrimp paste. This can be observed in some of the shrimp pastes sold at the Ciroyom market in Bandung, which are bright red, uneven, and comprised of lumps. This study aims to determine the Rhodamine B content of shrimp paste sold at Ciroyom Market in Bandung, West Java, Indonesia. This research is descriptive in nature and employed a total sampling technique. Rhodamine B was analyzed in ten samples of commercially available red shrimp paste using a UV-Vis Spectrophotometer with a 565 nm wavelength. The results indicate that Rhodamine B was found in all samples, with concentrations ranging from 1.79 ppm to 3.999 ppm. Therefore, it can be concluded that widespread abuse of Rhodamine B in food ingredients persists among the residents of Bandung City, West Java, Indonesia.